Buletin Peternakan : Suplementasi Hormon Gonadotropin Pada Medium Maturasi In Vitro Untuk Meningkatkan Perkembangan Embrio Stadium 4 Sel Kambing Bligon - Dewi Pranatasari, Kustono Kustono, Diah Tri Widayati (Peternakan UGM, 2016)
The study was carried out to investigate the effect of gonadotropin hormone supplementation into in vitro maturation medium on maturation, fertilization and embryo development of Bligon goats. This research steps consist of oocyte collection, in vitro maturation, in vitro fertilization, and in vitro embryo development.